Prevalencia de obesidad en pacientes pediátricos atendidos en el Hospital Minsa II-2 Tarapoto y Hospital Essalud II-2 Tarapoto y su relación con la circunferencia abdominal, periodo julio - noviembre 2015 - Linares Herrera, Yehude Darwy (2016)
Objective: To know the distribution and main parameters of obesity in pediatric patients attended at the MINSA II-2 Tarapoto Hospital and Hospital Essalud II-2 Tarapoto, July-November 2015. Materials and method: The study was carried out in the MINSA and ESSALUD Hospitals of the city of Tarapoto-San Martin. The study population consisted of 500 children, 250 of the MINSA hospital and 250 of the Essalud Hospital, from zero to 18 years of age, of both sexes, distributed in five age groups. Body mass index (BMI) values were analyzed according to the CDC tables, with diagnostic values between the 85th and 95th percentile for overweight and the 95th percentile for obesity. Values for abdominal circumference were analyzed according to Mc Carthy, in his study published in Jocn Eupean Journal of Clinical nutrition, having as diagnostic value an increased abdominal circumference above the 90th percentile. Results: A prevalence of 7.6% of overweight and 14.4% of obesity was found. According to sex, in males 69.1% were obese and overweight; In women, 30.9% were obese and overweight. There was greater obesity and overweight in the school age group (5-11 years) with 45.5%. According to the hospitals Essalud presented 60% with obesity and overweight, and the MINSA hospital 40%. Of the patients with obesity and overweight, 23.63% had increased abdominal circumference, and 76.37% had normal abdominal circumference. Conclusions: A prevalence of 7.6% of overweight and 14.4% of obesity was found. There was no significant relationship between obesity and overweight, with increased abdominal circumference